THE CURRENT STATE OF WOODY PLANT COMMUNITY GROWING NATURALLY ON THE DEVASTATED LANDS OF THE IRON DUMP (KRYVYI RIH) (Ecological Bulletin of Kryvyi Rih District, 2023)
The article presents the study results of the current condition of the dendrocenoses flora naturally distributed on the devastated lands of Petrivskyi iron ore dump. Taxonomic composition, life status of trees,dendrometric parameters of the studied species were investigated on the example of tree-shrub plant communities of disturbed lands. The researchwas conducted on devastated areas that were not rehabilitated. 22 species of woody plants (14 genera and 12 families) naturally grow within the temporary experimental plots of the Petrivskyi iron ore dump. Among them adventive species (63.6%) have a significant advantage compared to aboriginal species (36.4%) by quantitative indicators. The vitality of dendrophytocenosesnaturally distributed on the devastated lands of Petrivskyi iron ore dump was established according to three criteria: according to the indicators of the number of trunks (70.51±1.28 conditional points), trunk wood stocks (68.62±3.43 conditional points) and the sum of cross-sectional areas (67.39±2.98 conditional points). The current life status of woody plant species in the iron ore dump according to V. A. Alekseyev’s scale (1989) is estimated as “Weakened”: 65–71 conditional points. Such numerical values of the vitality of the trees are 21–28% lower than the control indicators (natural community of Gurivka forest). The trees dendrometric parameterson disturbed lands were established (planting density, average height and diameter, sum of cross-sectional areas, stock of trunk wood). In all researchedareas, which are characterized by a high level of pollution, the biometric parameters of trees are significantly lower compared to plants growing in a conditionally clean zone. Our results indicate that the ecological conditions of the devastated lands of Petrovsky dump are relatively favourable for the growth and development of woody and shrub plant species.
Keywords: tree species; vital condition; taxonomic composition; dendrometric indicators; devastated lands; Petrovsky iron ore dumps; Kryvyi Rih District